A technology acceptance and sociopedagogical perception survey of pre-service early childhood teachers’ use of generative AI for lesson planning - Manga, Delvhina; Islami, Andi Nur Maharani (Privietlab, 2026)
This study investigated pre-service early childhood teachers’ perceptions of generative AI in lesson planning. Using a quantitative descriptive design, 30 fifth-semester students completed an online questionnaire assessing perceived usefulness, perceived ease of use, ethical concerns, sociopedagogical factors, and attitudes toward AI, complemented by open-ended questions. Findings indicate that students perceive AI as highly useful and easy to use, particularly for generating ideas, structuring lesson content, and supporting pedagogical tasks. Ethical concerns were moderate, highlighting awareness of potential overdependence, content accuracy, and academic integrity issues, while sociopedagogical support, including guidance from lecturers, peers, and institutional resources, enhanced confidence and responsible use. Overall, participants demonstrated positive attitudes toward AI, appreciating its practical benefits while recognizing the need for ethical literacy and structured institutional support. The study provides insight into how generative AI can be integrated effectively into early childhood education, balancing innovation, professional judgment, and responsible use.